2019
DOI: 10.1002/cncr.31985
|View full text |Cite
|
Sign up to set email alerts
|

Lasting effects of cancer and its treatment on employment and finances in adolescent and young adult cancer survivors

Abstract: Background The impact of cancer and its treatment on employment and financial burden in adolescents/young adults (AYAs) is not fully known. Methods Eligibility for this cross‐sectional study of AYA cancer survivors included the diagnosis of a malignancy between ages 18 and 39 years and survey completion within 1 to 5 years from diagnosis and ≥1 year after therapy completion. Participants were selected randomly from the tumor registries of 7 participating sites and completed an online patient‐reported outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(69 citation statements)
references
References 19 publications
2
61
1
Order By: Relevance
“…Cancer survivors are vulnerable to financial hardships that may manifest as material (eg, problems paying medical bills, medical debt, and bankruptcy), psychological (eg, stress or worry about paying medical bills), or behavioral (eg, delaying or forgoing necessary medical care because of cost) aspects. Survivors who are younger, underinsured or uninsured, and/or have lower income are more likely to experience financial hardship, as are long‐term survivors of childhood cancer . For example, in one study, approximately 35% of cancer survivors aged 18 to 49 years reported difficulty in paying medical bills compared with 25% in those without a history of cancer; this gap narrowed substantially in those aged 50 to 64 years (27% vs 23%, respectively) .…”
Section: Quality Of Life and Other Concerns In Survivorshipmentioning
confidence: 99%
“…Cancer survivors are vulnerable to financial hardships that may manifest as material (eg, problems paying medical bills, medical debt, and bankruptcy), psychological (eg, stress or worry about paying medical bills), or behavioral (eg, delaying or forgoing necessary medical care because of cost) aspects. Survivors who are younger, underinsured or uninsured, and/or have lower income are more likely to experience financial hardship, as are long‐term survivors of childhood cancer . For example, in one study, approximately 35% of cancer survivors aged 18 to 49 years reported difficulty in paying medical bills compared with 25% in those without a history of cancer; this gap narrowed substantially in those aged 50 to 64 years (27% vs 23%, respectively) .…”
Section: Quality Of Life and Other Concerns In Survivorshipmentioning
confidence: 99%
“…In this regard, concerning the impact of different therapeutic cancer protocols in affecting work absenteeism, the mean duration of sick leave was significantly lower in patients with differentiated thyroid cancer who received rhTSH aided radioiodine ablative therapy (RIT) one week after thyroidectomy than in patients who received rhTSH aided RIT after 4-6 weeks following standard protocol [41]. Moreover, among the employed cancer survivors investigated by Ketterl et al [32], those who had been exposed to radiation were significantly more likely to need a long period of paid work rest compared to those who had not been exposed to radiation. In regards to possible effects of complications from common thyroid surgical procedures on sickness absence, patients experiencing hypoparathyroidism, vocal cord paralysis, as well as vocal cord paralysis and concomitant hypoparathyroidism reported 43, 115 and 97 days lost from work [42].…”
Section: Thyroid Diseases and Sick Leavementioning
confidence: 99%
“…Analysis of the data by gender showed a significantly higher risk of being unemployed only among women, and this finding was confirmed also when ethnic and education variables were analyzed. A more recent investigation reported that, among 126 survivors of thyroid cancer, 104 (82.5%) were employed sometime between the diagnosis and the study participation period [32]. Mongelli et al [33] reported that about a half of the 1753 investigated cancer survivors were employed full time, 10.6% had a part time employment, while the 4.8% reported being self-employed or a small business owner.…”
Section: Thyroid Disease and Employment Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of poor physical fitness are particularly concerning due to the negative implications they have on patients' and survivors' ability to fulfill basic life roles (e.g., activities of daily living, personal care). These functional and activity limitations can further lead to other negative consequences, such as poor overall quality of life (QOL), poor mental health, unemployment, financial toxicity, and related comorbidities and mortality [23,24]. However, there is no accepted standardized approach to the screening or treatment of PA and PF declines experienced in young cancer patients and survivors throughout the care continuum [25].…”
Section: Introductionmentioning
confidence: 99%